PHYTOCHEMICAL SCREENING, GC-MS AND FT-IR ANALYSIS OF METHANOLIC EXTRACT LEAVES OF ELETTARIA CARDAMOMUM - Khatri, Poonam; Rana, J.S.; Jamdagni, Pragati; Sindhu, Anil (International Journal of Research -GRANTHAALAYAH, 2017)
In this modern era, medicinal plants are at great attention to the researchers as most of the drug industries depend on medicinal plants for the production of therapeutic compounds. In many countries especially in India, plants are the conventional source of pharmaceutical biochemical, food colours, flavours and fragrances. Hence, the main aim of the study was the identification of bioactive compounds from the leaves of Elettaria cardamomum by Gas Chromatography and Mass spectroscopy (GC-MS). The GC-MS study revealed the presence of various compounds like Vitamin E, Squalene, Eucalyptol, Stigmast-5-en-3-ol, 4H-1-Benjopyran-4-one, 2,3-dihydro-5, 7-dihydroxy-2-pheny, Octadecanoic acid, Phytol, Hexadecanoic acid in the methanolic extract of Elettaria cardamomum. Henceforth, the Elettaria cardamomum may have chemo preventive, antidiabetic, anti- microbial and anticancer activity due to the presence of secondary metabolites in the methanolic extract. The results of FTIR analysis confirmed the presence of alcohol, phenols, alkanes, alkyl halides and alkynes. In the present study, leaf sample of this plant was analyzed for the first time. This work will help to identify the active components, which may be used for therapeutic purposes. This study offers a platform of using Elettaria cardamomum leaves as herbal alternative for many diseases.